TECHNOLOGY OF FORMATION OF STUDENT TEAM OF HIGHER EDUCATIONAL INSTITUTION (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the upbringing technology of high school “The formation of student’s association” .Positive and negative factors of the student’s collectives development have been analyzed. The sense of diagnpstication in the process of technology realization has been shown. Methods which help wish the student’s collective groping has been determined.
Keywords: educational technologies; upbringing technologies; technology of the formation of the students’ association, diagnostics